High hemolytic activity in Staphylococcus aureus t1081/ST45 due to increased hla protein production and potential RNAIII-independent regulation - Yu-Tzu Lin; Ngoc-Niem Bui; Yu-Syuan Cheng; Cheng-Wen Lin; Chun-Li Lee; Tai-Fen Lee; Po-Ren Hsueh (Journal of Microbiology, Immunology and Infection)
Background: α-Hemolysin, encoded by hla, is a major virulence factor of Staphylococcus aureus. Sequence type (ST) 45 is a globally spread clone with increasing clinical prevalence in Taiwan. Our previous study showed that among the CC45 isolates, the spa type t1081 isolates presented greater hemolytic activity. Materials and methods: The hemolytic activity of 67 CC45 isolates (44 t1081 and 23 non-t1081) from clinical blood cultures was assessed using rabbit red blood cells. The sequences of hla and its upstream regulatory regions and RNAIII were compared between the two groups. The expression of hla and its regulators RNAIII, mgrA, and saeR was analyzed via qRT‒PCR, while Hla protein levels were measured via Western blotting. Results: Compared with non-t1081 isolates, t1081 isolates presented increased hemolytic activity. No significant differences in hla sequences, upstream regulatory regions, or gene expression levels were detected between the two groups. The expression of the transcriptional regulators mgrA and saeR was also similar between the two groups. Western blotting revealed increased Hla protein in the t1081 isolates. However, neither the sequence or expression of RNAIII, a regulator of hla at both the transcriptional and posttranscriptional levels, differed between the groups. Conclusion: Our study revealed that, compared with other CC45 isolates, the t1081/ST45 isolates presented greater hemolytic activity. This heightened activity was due mainly to increased Hla protein levels. Moreover, the higher translation levels may be independent of the known regulator RNAIII, indicating a potential RNAIII-independent mechanism for Hla regulation.